Ultrasound teaching manual : the basics of performing and interpreting ultrasound scans - Hofer, Matthias; Winter, Peter F (Thieme, 1999)
Suitable for radiology residents and radiographers, this \"workbook\" is a useful guide in approaching ultrasound scanners. Designed as a self-learning tool, it introduces the various applications of US scanners according to organs, including positioning, step-by-step descriptions of the procedure, representative ultrasound scans, explanatory drawings and an overview of the most important measurement data. Finally, a self-assessment checklist at the end of each chapter should help readers to monitor their progress and evaluate their knowledge.
Keywords: ultrasonografie; Ultrasonography; radiologie, nukleární medicína a zobrazovací metody